Insight into the role of weak interaction played in the fixation of CO2 catalyzed by the amino-functionalized imidazolium-based ionic liquids. (March 2017) - Chen, Ci; Ma, Yuan; Zheng, Danning; Wang, Li; Li, Junfeng; Zhang, Jinglai; He, Hongyan; Zhang, Suojiang
Graphical abstract: Highlights: The mechanism of amino-functionalized imidazolium-based IL for fixation of CO2 . The mechanism catalyzed by multi-species is considered. Positive charge is not the sole item to determine the electrophilic attack. Ring-opening is promoted by both weak interaction and electrostatic interaction. Abstract: The mechanism of coupling reaction of CO2 with propylene oxide (PO) catalyzed by the amino-functionalized imidazolium-based ionic liquid is theoretically investigated by the density functional theory (DFT). Although the mechanisms of the fixation of CO2 catalyzed by various room-temperature ionic liquids or functionalized ionic liquids have been theoretically elucidated in previous literatures, it is not totally suitable for the amino-functionalized ionic liquid. First, the 1-(3-aminopropyl)-3-methylimidazolium chloride ([APmim]Cl) would react with CO2 to produce the 1-(3-carbamic acid propyl)-3-methylimidazolium chloride ([CAPmim]Cl). Then, [APmim]Cl, [CAPmim]Cl, and combination of them would be employed as the catalyst leading to nine possible routes. Different from the previous work, this work allows a better comprehension of the mechanism by means of a new model that the cooperative effect of two same or different components is considered. Both the interaction between catalyst and reactant and the influence between different catalytic components are considered. Besides the nucleophilic attack of the Cl − anion, the [CAPmim] + cation is taken as the main component to activate the O atom of PO directly leading to the ring-opening. The [APmim] + cation is utilized to stabilize the [CAPmim] +, which is the most favorable route. The noncovalent interactions (NCI) plot is employed as a tool to analyze the reason of the higher catalytic efficiency of top three favorable routes. The hydrogen bond and dispersive attractive interaction is confirmed to play a determining role in the catalytic activity.